A new algorithm for the evaluation of recurrent pregnancy loss redefining unexplained miscarriage: review of current guidelines. Issue 5 (October 2020) - Papas, Ralph S.; Kutteh, William H.
Abstract : Purpose of review: Couples with recurrent pregnancy loss (RPL) are often referred to reproductive specialists to help determine the reason for their repeated losses. This review will help to develop a strategy that is effective in providing a diagnosis, efficient to administer, and cost-effective to the healthcare system. Recent findings: International societies have published different recommendations for the evaluation of RPL, they consider it appropriate to initiate an evaluation after two (or three) clinical miscarriages. On the contrary, the clinician who follows these guidelines will only be able to offer a possible explanation to fewer than half of the couples being evaluated. Recently, genetic testing of miscarriage tissue using 24-chromosome microarray (CMA) analysis at the time of the second pregnancy loss coupled with testing based on society guidelines has been shown provide an explanation in more than 90% of cases. Summary: New guidelines for the complete evaluation of RPL should consider adding 24-CMA testing on the miscarriage tissue. Providing couples with an explanation for recurrent loss assists them in dealing with the loss and discourages the clinician from instituting unproven therapies. Truly unexplained pregnancy loss can be reduced to less than 10% with this new algorithm. Incorporation of these strategies will result in significant cost savings to the healthcare system.